2021
DOI: 10.18632/aging.202642
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib alleviates zinc deficiency-promoted colon tumorigenesis through suppressing inflammation

Abstract: Accumulating evidence has shown that dietary zinc deficiency (ZD) increases the risk of various cancers including esophageal and gastric cancer. However, the role of ZD in colon tumorigenesis is unknown and the related mechanisms need to be investigated. Apc min/+ mice, widely used to mimic the spontaneous process of human intestinal tumor, were used to construct a ZD mice model in this study. Inflammatory mediators such as COX-2, TNF-α, CCL, CXCL, and IL chemokines families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Use of the zinc chelator, N , N , N′ , N′ tetrakis(2-pyridinylmethyl)-1,2-ethanediamine reduces the LPS-induced increase in the formation of NLRP3-level IL-1β, while reducing neuronal death [ 41 ]. In addition, nutritional zinc deficiency can increase the levels of the inflammatory factors, CCL2, CXCL2, CXCL5, IL-1, IL-6, and TNF-α in the serum and in colonic mucosa, accelerating the development of colonic tumors [ 42 ]. In animal experiments, zinc supplementation of 120 mg/kg improved the growth performance of Pekin ducks; it reduced intestinal damage and increased intestinal enzyme activity.…”
Section: Zinc and Agingmentioning
confidence: 99%
“…Use of the zinc chelator, N , N , N′ , N′ tetrakis(2-pyridinylmethyl)-1,2-ethanediamine reduces the LPS-induced increase in the formation of NLRP3-level IL-1β, while reducing neuronal death [ 41 ]. In addition, nutritional zinc deficiency can increase the levels of the inflammatory factors, CCL2, CXCL2, CXCL5, IL-1, IL-6, and TNF-α in the serum and in colonic mucosa, accelerating the development of colonic tumors [ 42 ]. In animal experiments, zinc supplementation of 120 mg/kg improved the growth performance of Pekin ducks; it reduced intestinal damage and increased intestinal enzyme activity.…”
Section: Zinc and Agingmentioning
confidence: 99%
“…Bothe specific and non-specific inhibitors of COX-2, such as nonsteroidal anti-inflammatory drugs (NSAIDs), can induce apoptosis of gastric cancer, colorectal cancer, and pancreatic cancer cells ( 34 ). A study on esophageal cancer showed celecoxib could inhibit the expression of COX-2, down regulate the expression of PGE, inhibit the proliferation of esophageal cancer cells, and improve the therapeutic effect of chemotherapy and radiotherapy ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that, certain trace element deficiencies may cause the cancer to grow. Zinc deficiency, for example, significantly promotes the mRNA and protein levels of CCL2, CXCL2, and CXCL5 in the colonic mucosa and tumorigenesis in the colon (122).…”
Section: Chemokines Act As Bridges Between Some Extrinsic Factors And...mentioning
confidence: 99%